Negative Ion Formation in Potassium-Purine Molecules collisions - Cunha, Tiago Miguel da Fonseca (2018)
The research described in this thesis focuses on the study of electron transfer mechanisms in purine molecules and derivatives (adenine, 9-methyl adenine, 6-dimethyl adenine and 2-D adenine), in potassium-molecule collisions. The studies were performed in a crossed beam experiment, comprising a neutral potassium beam and a biomolecular effusive beam with a time-of-flight mass spectrometer and a recently implemented hemispherical analyser, yielding an experimental arrangement capable of providing relevant information of the collision dynamics. From this comprehensive investigation, we report for the first time, collision induced site and bond selective breaking in purine molecules by alkali collisions. The influence of the K+ ion in the vicinity of the temporary molecular anion was also investigated, indicating to partially suppress auto-detachment resulting in new or enhanced dissociation pathways. Concerning the energy loss set-up, we present in the 0 to 15 eV energy range novel K+ profiles in the forward direction ( 0 ) from fast potassium collisions with nitromethane and tetrachloromethane where new features are unravelled, and reported for the first time as far as akali collisions are concerned. Due to the current configuration, it restricts the use of this technique exclusively to samples with high vapour pressure. The potassium beam energy resolution was determined to be 0.6 eV in the laboratory frame.